Human Microbiome and Its Medical Applications - Zhang, Yangming; Zhou, Linguang; Xia, Jialin; Dong, Ce; Luo, Xiaozhou (Frontiers in Molecular Biosciences, 2022)
The commensal microbiome is essential for human health and is involved in many processes in the human body, such as the metabolism process and immune system activation. Emerging evidence implies that specific changes in the microbiome participate in the development of various diseases, including diabetes, liver diseases, tumors, and pathogen infections. Thus, intervention on the microbiome is becoming a novel and effective method to treat such diseases. Synthetic biology empowers researchers to create strains with unique and complex functions, making the use of engineered microbes for clinical applications attainable. The aim of this review is to summarize recent advances about the roles of the microbiome in certain diseases and the underlying mechanisms, as well as the use of engineered microbes in the prevention, detection, and treatment of various diseases.